Determining Factors of Organizational Culture, Leadership Style and Communication on Employee Performance in Direktorat Pengelolaan Lahan - Nidel, Muhammad Ihsan; Lubis, Laily Rozanna (Zona Manajerial: Program Studi Manajemen (S1), 2023)
The primary objective of this study is to delve into and dissect the intricate relationship between organizational culture, leadership approaches, communication practices, and the overall performance of employees within the BP Batam Land Management Directorate. By employing a comprehensive approach, this research endeavors to shed light on how these key factors interplay and impact the efficiency and effectiveness of the workforce. To accomplish this, data was meticulously gathered from 145 employees via structured questionnaires, providing valuable insights into their perceptions and experiences. Leveraging the robust statistical capabilities of the SPSS application, the collected data underwent rigorous analysis. Validity and reliability tests, including the esteemed Cronbach Alpha assessment, were employed to ensure the integrity and accuracy of the findings. The culmination of this analysis revealed compelling results. Notably, the coefficient of determination (R2) highlighted that a significant portion, accounting for 22.7%, of employee performance variation can be attributed to factors such as compensation, organizational culture, leadership style, and communication practices. However, it is noteworthy that 77.3% of employee performance is influenced by other variables not encompassed within this study, underscoring the multifaceted nature of workforce dynamics.